POSI BOLA OF JAMI MOSQUE AS SPATIAL TRANSFORMATION SYMBOL - sutrisno, moh; Sastrosasmito, Sudaryono; Sarwadi, Ahmad (Journal of Islamic Architecture, 2019)
Palopo city space as the center of Tana Luwu cannot be separated from the significance of the oldest kingdom in South Sulawesi. The entry of the Islamic religion in Luwu was marked by the Jami Mosque, which is located at the zero points of Palopo city. The preservation of pre-Islamic heritage and after the entry of Islam in the present tends to not a dichotomy in two different meanings. The research is aimed to explore the semiotic meaning of the Jami Mosque, which has become an icon in Palopo City. The research used the ethnomethodology method within the framework of the semiotics paradigm to obtain contextual meaning as well as the application of a new approach in architecture semiotics study. The results show that the Jami Mosque keeps the complexity of meaning, which can be the foundation of conservation philosophy and planning of the built environment. The cosmos axis of Palopo city space and the territory of Luwu become the central point of religious civilization, especially in Islamic cosmology. The space transformation is represented by ‘posi bola’ (house pole). The symbolic ‘posi bola’ moves from the palace to the Jami mosque as the axis of Luwu space in the Islamic era. The horizontal slice of the pole has implications on the particular geometrical patterns of Luwu. The elements of structure and construction of buildings become a symbol of Islamic teachings.